Effect of ethanol addition on the properties of Jatropha ethyl ester. Issue 23 (1st December 2016) - Gautam, Raghvendra; Kumar, Naveen
ABSTRACT: Fossil fuels are available in limited quantity and may extinct in future. Moreover, pollutant emission from diesel engines affects the ecological systems. Biodiesel, derived from vegetable oil, is a renewable and green source of fuel. In this study, biodiesel produced from base catalyzed transesterification was blended with different diesel volumes. The diesel–biodiesel blends showed varied flash point (168–42°C), viscosity (4.34–3.31 mm 2 /s), density (0.872–0.8351 g/cm 3 ), acid value (0.3–0.4 mg KOH/g), and cetane number (51.6–49.5). The results showed that alcohol addition helped in reducing viscosity and density of biodiesel by almost half. These provide explanation on engine performance, combustion, and emission characteristics.